The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1172/jci124516
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic ploidy changes drive fluconazole resistance in human cryptococcal meningitis

Abstract: BACKGROUND. Cryptococcal meningitis (CM) causes an estimated 180,000 deaths annually, predominantly in sub-Saharan Africa, where most patients receive fluconazole (FLC) monotherapy. While relapse after FLC monotherapy with resistant strains is frequently observed, the mechanisms and impact of emergence of FLC resistance in human CM are poorly understood. Heteroresistance (HetR) — a resistant subpopulation within a susceptible strain — is a recently described phenomenon in Cryptococcus ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
142
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(156 citation statements)
references
References 53 publications
2
142
0
1
Order By: Relevance
“…Cryptococcus neoformans displays fluconazole hetero-resistance: transient resistance in a subpopulation of cells mediated by aneuploidy of chromosomes that carry genes involved in fluconazole detoxification, and this impacts on disease outcomes (5558). Gerstein et al previously demonstrated that in vivo- derived titans provide daughters with a survival advantage compared to in vivo- derived typical cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptococcus neoformans displays fluconazole hetero-resistance: transient resistance in a subpopulation of cells mediated by aneuploidy of chromosomes that carry genes involved in fluconazole detoxification, and this impacts on disease outcomes (5558). Gerstein et al previously demonstrated that in vivo- derived titans provide daughters with a survival advantage compared to in vivo- derived typical cells.…”
Section: Discussionmentioning
confidence: 99%
“…above discussed, the antifungal of choice are different, as fluconazole is indicate for Cryptococcus sp. while yeasts of the genus Rhodotorula are resistant to this antifungal class [43]. It is important to note that yeasts belonging to Rhodotorula genus have a high level of fluconazole resistance, a greater tolerance for itraconazole and susceptibility for amphotericin B [44, 45].…”
Section: Discussionmentioning
confidence: 99%
“…These microevolutionary changes have been documented in AIDS patients with chronic and recurrent cryptococcal infections (12)(13)(14)(15)(16), as well as in murine models of infection (13,16). Resulting phenotypes include resistance to azole drugs (12,14) and differences in capsule structure, melanization and thermotolerance (12,13,17,18), all of which are factors that increase persistence of Cryptococcus in the host. In addition, up to 20% of cryptococcal cells form giant polyploid cells (titan cells) during infection that are resistant to phagocytosis and have enhanced survival and dissemination (19,20).…”
Section: Introductionmentioning
confidence: 99%
“…In response, these fungi can undergo rapid genomic adaptations that enhance survival and enable drug resistance (11). Previously reported alterations arising during cryptococcal infection include base substitutions, insertions, deletions, target gene copy-number variation, and chromosomal duplications (12)(13)(14). These microevolutionary changes have been documented in AIDS patients with chronic and recurrent cryptococcal infections (12)(13)(14)(15)(16), as well as in murine models of infection (13,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation